INFLUENCE OF INTEREST RATE, INFLATION, NET INCOME AND CORPORATE LOANS ON DIVIDENDS DISTRIBUTION - Maya Sabirina Panggabean; Gonzales Narwastu; Kartika Deasi Putri Zebua; Tiurnida Sinurat; Eti Hayati (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to explain the effect of the variables of Interest Rate, Inflation, Net Profit, and Corporate Debt on the Dividend Distribution of the Banking sub-sector on the Indonesia Stock Exchange for the 2017-2020 period. This study uses a sample of 40 banking sub-sector companies on the IDX in 2017-2020. This research is quantitative research. The data used is secondary data obtained from the IDX for the 2017-2020 period. The sample selection method is purposive sampling. The data investigation method used is the multiple linear regression method. The results of the study prove that interest rates, inflation, and company debt have no partial effect on dividends, while net income partially affects dividends. Based on the simultaneous interest rate, inflation, net profit, and company debt, it does not have a significant effect on the Dividend Distribution of the Banking sub-sector on the Indonesia Stock Exchange for the 2017-2020 period